Loading noise effects on the system identification of composite structures by dynamic tests with vibrodyne. (15th April 2017) - Fabbrocino, F.; Farina, I.; Modano, M.
Abstract: The design of new composite structures, and the system identification of existing structures strengthened through the application of composite materials, often require dynamic tests executed with the assistance of accurate forcing devices. The present paper presents a characterization of the force time-histories that can be applied through a vibrodyne, an electro-mechanical excitation machine that is able to generate vibrations, with known frequency and amplitude. Such a device is frequently employed when dealing the experimental modal analysis of composite structures at different scales. We conduct an experimental study on the forcing functions generated by a vibrodyne, and the mismatches between such loading histories and the theoretical sinusoidal profiles. Next, we study the effects of such mismatches on the simulated dynamic response of a simple structural model. Based on the results of such a study, we outline a procedure for building up a database of the real forcing functions applied by a vibrodyne, over a wide range of operating conditions. Such a tool can play a key role when conducting dynamical tests on next-generation composite structures through vibrodyne.